What constitutes “behavioral health”? Perceptions of substance-related problems and their treatment in primary care - Ida Q. Chen; Helene Chokron Garneau; Timothy Seay-Morrison; Megan R. Mahoney; Heather Filipowicz; Mark P. McGovern (Addiction Science & Clinical Practice, 2020)
Abstract Background Integrating behavioral health in primary care is a widespread endeavor. Yet rampant variation exists in models and approaches. One significant question is whether frontline providers perceive that behavioral health includes substance use. The current study examined front line providers’: 1. definition of behavioral health, and 2. levels of comfort treating patients who use alcohol and other drugs. Frontline providers at two primary care clinics were surveyed using a 28-item instrument designed to assess their comfort and knowledge of behavioral health, including substance use. Two questions from the Integrated Behavioral Health Staff Perceptions Survey pertaining to confidence in clinics’ ability to care for patients’ behavioral health needs and comfort dealing with patients with behavioral health needs were used for the purposes of this report. Participants also self-reported their clinic role. Responses to these two items were assessed and then compared across roles. Chi square estimates and analysis of variance tests were used to examine relationships between clinic roles and comfort of substance use care delivery. Results Physicians, nurses/nurse practitioners, medical assistants, and other staff (N = 59) participated. Forty-nine participants included substance use in their definition of behavioral health. Participants reported the least comfort caring for patients who use substances (M = 3.5, SD = 1.0) compared to those with mental health concerns (M = 4.1, SD = 0.7), chronic medical conditions (M = 4.2, SD = 0.7), and general health concerns (M = 4.2, SD = 0.7) (p < 0.001). Physicians (M = 3.0, SD = 0.7) reported significantly lower levels of comfort than medical assistants (M = 4.2, SD = 0.9) (p < 0.001) caring for patients who use substances. Conclusions In a small sample of key stakeholders from two primary care clinics who participated in this survey, most considered substance use part of the broad umbrella of behavioral health. Compared to other conditions, primary care providers reported being less comfortable addressing patients’ substance use. Level of comfort varied by role, where physicians were least comfortable, and medical assistants most comfortable.